2019
DOI: 10.1111/bjh.15756
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the monitoring of direct oral anticoagulant therapy

Abstract: Summary The availability of direct oral anticoagulants (DOACs) has led to a paradigm shift in the field of anticoagulation, with DOACs increasingly being prescribed for patients in preference to vitamin K antagonists and low molecular weight heparin. Despite good experience with the use of these agents at fixed doses, there are clinical scenarios where monitoring is recommended. Data from phase III studies of the DOACs and small real‐world studies suggest a relationship between DOAC concentration and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 73 publications
1
46
0
1
Order By: Relevance
“…Our study showed a relatively high interindividual variability for the two measured DOACs, higher for rivaroxaban than apixaban and higher for trough than peak levels, in line with data in literature . The interpatient variability was similar among the chromogenic assays and HPLC‐UV, except for the method antithrombin‐supplemented whose results were influenced by the high LOQ, especially for rivaroxaban.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study showed a relatively high interindividual variability for the two measured DOACs, higher for rivaroxaban than apixaban and higher for trough than peak levels, in line with data in literature . The interpatient variability was similar among the chromogenic assays and HPLC‐UV, except for the method antithrombin‐supplemented whose results were influenced by the high LOQ, especially for rivaroxaban.…”
Section: Discussionsupporting
confidence: 90%
“…The assay's sensitivity and detection thresholds in terms of limits of detection (LOD) and quantification (LOQ) are method‐dependent, but the use of low‐range calibrators demonstrated to improve the assay's sensitivity for low plasma concentrations. They have been recommended as suitable methods to provide a rapid quantification of direct FXa inhibitor concentrations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, population pharmacokinetics will allow Monte Carlo simulations to be carried out to test different hypotheses without the need to involve new patients [62]. In the absence of PK/PD reference markers that would predict the occurrence of haemorrhagic or thrombotic clinical events [63], prospective follow‐up of treated patients should be conducted to determine the risk benefit balance of DOACs in this population.…”
Section: Prospects For the Futurementioning
confidence: 99%
“…12 In this regard, thrombin generation tests (thrombin clotting time or ecarin clotting time) or thromboelastography may perform better compared with the INR for predicting bleeding risk, but is used for monitoring anticoagulant therapy in routine clinical practice. 13,14 In general, target INR for patients with cirrhosis is a goal INR of 1.0 higher than baseline, if the baseline INR is >1.5. Vitamin K, prothrombin complex concentrates, and fresh frozen plasma can be used to reverse bleeding in patients receiving warfarin.…”
Section: Review Maintenance Of Anticoagulationmentioning
confidence: 99%